2019
DOI: 10.1021/acsaem.9b01979
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Coupling of a Molybdenum Carbide Nanosphere with Pt Nanoparticles for Enhanced Ammonia Electro-Oxidation Activity in Alkaline Media

Abstract: Ammonia will play a pivotal role in the future of zero carbon emitted sustainable fuel. The development of inexpensive efficient catalysts for ammonia electro-oxidation (AEO) is essential to its success. This study provides evidence that nanoparticles of earth-abundant elements, e.g. MoC, encapsulated in a doped-graphene shell (DG-MoC) are promising co-2 catalysts of Pt for AEO which significantly improves the catalyst cost and activity in comparison to the state of art platinum. DG-MoC, DG-MoC-supported Pt (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 66 publications
(138 reference statements)
0
4
0
Order By: Relevance
“…Recently, electrocatalytic oxidation of ammonia (AEO) has attracted much attention of researchers and scientists because, as a hydrogen-rich carrier, it possesses 70% higher volumetric hydrogen content than pure liquid hydrogen [5,6]. Theoretical and experimental investigations reveal that hydrogen generation via ammonia electro-oxidation (AEO) is a cost-effective approach compared to water electrolysis because it requires much lower oxidation potential (0.06 V) than water (−1.23 V), as described in Equations (1-3) [7,8]. Theoretical ammonia electrolysis consumes energy of about~1.55 Wh•g −1 H 2 at standard conditions, which is 95% less than water electrolysis [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, electrocatalytic oxidation of ammonia (AEO) has attracted much attention of researchers and scientists because, as a hydrogen-rich carrier, it possesses 70% higher volumetric hydrogen content than pure liquid hydrogen [5,6]. Theoretical and experimental investigations reveal that hydrogen generation via ammonia electro-oxidation (AEO) is a cost-effective approach compared to water electrolysis because it requires much lower oxidation potential (0.06 V) than water (−1.23 V), as described in Equations (1-3) [7,8]. Theoretical ammonia electrolysis consumes energy of about~1.55 Wh•g −1 H 2 at standard conditions, which is 95% less than water electrolysis [9].…”
Section: Introductionmentioning
confidence: 99%
“…To commercialize this direct ammonia fuel cell (DAFC) technology, an efficient, stable, and economical electrocatalyst is required. Thus far, expensive noble metal-based (Pt, Ru, Ir, Rh, Pd) alloys are considered as the best performing AEO catalysts [5][6][7][8]15,16]. Sluggish reaction kinetics of AEO, high cost and low resistance to poisoning by reaction intermediates of these catalysts hinder this technology in commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…13 During the survey scan of Mo-ECs (MoN, Mo 2 C, and MoS 2 ) nanomaterials, MoO x phases (MoO 2 and MoO 3 ) were also detected, which suggests that Mo species were either oxidized during the synthesis process or absorbed or contaminated by atmospheric oxygen [32,50,56,95,96]. Bayati et al [97] suggested that various oxidation states, such as Mo 2+ , Mo 3+ , Mo 5+ , and Mo 6+ as in a single Mo, can be linked to the presence of carbide, nitride, and oxide species, respectively [97,98]. A positive shift of 0.2 eV compared to the Pt 4f 7/2 of pure Pt can be attributed to an induced positive charge on the dis-…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 98%
“…In response to restraining the activity loss of nickel‐based catalysts, the contribution of metal compounds (e.g., MO x , [ 65 ] M(OH) x , [ 90 ] MC x [ 91 ] ) to their doping modification was also studied. Huang et al reported a nanostructured catalyst of Cu 2 O wire‐in‐Ni(OH) 2 plate passivated by a thin CuO surface, which can stably electrolyze alkaline ammonia solution into hydrogen and nitrogen at a high current density of 80 mA cm −2 ( Figure a,f).…”
Section: Electrocatalysts For the Aormentioning
confidence: 99%